Development Use Cases for Semantics-Driven Modeling Languages: Choosing underlying semantic theories and definition techniques must closely follow intended use cases for the modeling language. - BROY, MANFRED; RUMPE, BERNHARD (Communications of the ACM, 2023)
The article discusses designing programming languages by using semantic concepts and inherent theories rather than syntactic constructs alone. The relationship and interaction between semantics and syntax is reviewed. The author mentions that this approach to modeling has the ability to enhance software and systems development because it defines the behavior and meaning of the programming language constructs.